Chemotherapy of experimental streptococcal endocarditis: Part III Failure of a bacteriostatic agent (tetracycline) in prophylaxis - Southwick, Frederick S. (1974)
Bacteriostatic agents are frequently recommended as alternatives to penicillin for prophylaxis of bacterial endocarditis. To test the efficacy of this group of antimicrobials, prophylaxis of experimental streptococcal endocarditis was attempted with tetracycline. The number of streptococci colonizing the aortic valves of rabbits was not affected by inhibitory levels of tetracycline, but multiplication was checked. Streptococcis urvived in vegetations for seven days despite the continuous presence of tetracycline, and multiplied when the drug was withdrawn. It is therefore suggested that bacteriostatic agents may be valueless for prophylaxis of bacterial endocarditis.